A PORTRAYAL OF MULTILINGUAL PRACTICES IN MADURA TOURIST DESTINATIONS - Misnadin, Misnadin (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2023)
Multilingual practice is valuable for potential and established tourists as it can help promote the tourism industry. This study aims to describe the opinions of the Madurese people about the use of multilingual languages in Madura tourist destinations. The researcher collected data by distributing questionnaires about the use of Madurese, Indonesian, and English to respondents in the four districts of Madura; Bangkalan, Sampang, Pamekasan, and Sumenep. Questionnaires were analyzed based on the answers given by the respondents to the questions. The results show that tourist destinations in Madura ought to use three languages. The multilingual practices influence the tourism sector in Madura. Especially when the tourism stakeholders master several languages, more tourists may visit Madura and other tourist destinations.